EVALUASI KINERJA INSTALASI PENGOLAHAN AIR LIMBAH RUMAH SAKIT X KOTA SURABAYA - Mohammad Zidan R; Raden Kokoh. H.P (Yayasan Nusantara Hasana Berdikari, 2023)
Hospitals as institutions that provide health services to the community always produce liquid waste from each of their operational activities. Wastewater at the Wastewater Treatment Plant (IPAL) Hospital X has the characteristics of Temperature, Total Suspended Solid (TSS), pH, Biological Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), free ammonia (NH3-N), phosphate and total coliform. The purpose of this study was to evaluate the performance of WWTPs and to determine the content of wastewater after processing according to quality standards referring to East Java Governor Regulation No. 72 of 2013. The wastewater treatment system in RS. Hospital X uses a biological system. The data used in the analysis is secondary data on the parameters of the quality and quantity of wastewater at the inlet and outlet of the WWTP from January 2022 to October 2022. Based on the results of testing the quality and quantity of wastewater at the WWTP outlets of Hospital X, the wastewater content at the WWTP outlets is in accordance with with reference quality standards. In addition, the effectiveness of using biofilters in WWTP Hospital X succeeded in reducing the content of TSS 92%, 94% BOD5, 82% COD, 85% free Ammonia, 98% total coliform and 37% Phosphate. In addition, there was also an increase in temperature of 1% and an increase in pH value of 8%.